2021
DOI: 10.24191/mjoc.v6i1.11212
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Anomalies: A Case of Calendar Effects on the Malaysian Stock Market

Abstract: The existence of market anomalies for the return reveals the inefficiency in the market that could affect investor investment strategy, portfolio selection, and profit management. It is due to the unpredictable movement of the stock market return that will affect the decision of investors later. As such, this study intends to investigate day of the week effect, a month of the year effect, and a quarter of the year effect on the Malaysian Stock Exchange, namely the Kuala Lumpur Composite Index (KLCI) on data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They also found the existence of the December effect and the March effect and stated that the stock prices were higher on Friday compared to Monday. Furthermore, over the examination period from January 2015 to December 2018, Shariff et al (2021) found a significant month effect in Bursa Malaysia in May, November, and December.…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…They also found the existence of the December effect and the March effect and stated that the stock prices were higher on Friday compared to Monday. Furthermore, over the examination period from January 2015 to December 2018, Shariff et al (2021) found a significant month effect in Bursa Malaysia in May, November, and December.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Furthermore, over the examination period from January 2015 to December 2018, Shariff et al (2021) found a significant month effect in Bursa Malaysia in May, November, and December. Hasan et al (2021) examined the effects of seven calendar anomalies:(1) January;…”
Section: Literature Reviewmentioning
confidence: 88%